2022
DOI: 10.3390/ijms23020727
|View full text |Cite
|
Sign up to set email alerts
|

Role of Palatine Tonsil and Epipharyngeal Lymphoid Tissue in the Development of Glomerular Active Lesions (Glomerular vasculitis) in Immunoglobulin A Nephropathy

Abstract: Hematuria is an essential symptom of immunoglobulin A nephropathy (IgAN). Although the etiology of hematuria in IgAN has not been fully elucidated, it is thought that the rupture of the glomerular basement membranes caused by intra-capillary leukocyte influx, so-called glomerular vasculitis, is the pathological condition responsible for severe hematuria. Glomerular vasculitis are active lesions that exist in the glomeruli of acute phase IgAN and it is important because it is suspected to make the transition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Similar to COVID 19, upper respiratory tract infections (URTIs) of viral etiology begin in the epipharynx [ 32 , 33 ]. Chronic epipharyngitis, which may be secondary to URTI, is considered a residual immune response and causes not only various upper respiratory tract symptoms, such as postnasal drip, throat pain, and cough, but also systemic symptoms, such as chronic fatigue, headache, systemic pain, and dizziness [ 12 , 13 , 31 , 32 ]. Some of these systemic symptoms resemble those of MS/CFS, and chronic epipharyngitis is reported to activate epipharyngeal inner immunity and produce neuroexcitatory molecules, such as TNF-α, IFN-γ, and IL-1, which activate the immune system of the brain, resulting in low-grade inflammation in the brain associated with MF/CFS [ 12 , 13 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar to COVID 19, upper respiratory tract infections (URTIs) of viral etiology begin in the epipharynx [ 32 , 33 ]. Chronic epipharyngitis, which may be secondary to URTI, is considered a residual immune response and causes not only various upper respiratory tract symptoms, such as postnasal drip, throat pain, and cough, but also systemic symptoms, such as chronic fatigue, headache, systemic pain, and dizziness [ 12 , 13 , 31 , 32 ]. Some of these systemic symptoms resemble those of MS/CFS, and chronic epipharyngitis is reported to activate epipharyngeal inner immunity and produce neuroexcitatory molecules, such as TNF-α, IFN-γ, and IL-1, which activate the immune system of the brain, resulting in low-grade inflammation in the brain associated with MF/CFS [ 12 , 13 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic epipharyngitis, which may be secondary to URTI, is considered a residual immune response and causes not only various upper respiratory tract symptoms, such as postnasal drip, throat pain, and cough, but also systemic symptoms, such as chronic fatigue, headache, systemic pain, and dizziness [ 12 , 13 , 31 , 32 ]. Some of these systemic symptoms resemble those of MS/CFS, and chronic epipharyngitis is reported to activate epipharyngeal inner immunity and produce neuroexcitatory molecules, such as TNF-α, IFN-γ, and IL-1, which activate the immune system of the brain, resulting in low-grade inflammation in the brain associated with MF/CFS [ 12 , 13 , 34 , 35 , 36 , 37 ]. In this study, we found that 90% of long COVID patients had moderate or severe chronic epipharyngitis and that all patients complained of either fatigue, headache, attention disorder, or a combination of the three, confirming the findings of other reports on long COVID ( Figure 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations